2000
DOI: 10.1136/bmj.321.7275.1516
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from "Clinical Evidence": Menopausal symptoms

Abstract: Clinical Evidence search and appraisal December 1999. We included only randomised controlled trials (RCTs) and systematic reviews that met Clinical Evidence quality criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 34 publications
0
41
0
5
Order By: Relevance
“…However, serum CA15-3 level showed a non-significant increase within elderly menopause patients with breast cancer, in contrast to what was reported by Dehaghani et al, (2007) who found statistically significant values. Aging and menopause usually disturb immunity and hormonal status (Pike et al, 2004;Rymer & Morris, 2000). So screening this marker is recommended for females above forty years since Jordanian develop breast cancer at a much younger age (median age is 51) than women in Western countries (median age is 65) (Jordan breast cancer program, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, serum CA15-3 level showed a non-significant increase within elderly menopause patients with breast cancer, in contrast to what was reported by Dehaghani et al, (2007) who found statistically significant values. Aging and menopause usually disturb immunity and hormonal status (Pike et al, 2004;Rymer & Morris, 2000). So screening this marker is recommended for females above forty years since Jordanian develop breast cancer at a much younger age (median age is 51) than women in Western countries (median age is 65) (Jordan breast cancer program, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…CA15-3 level increased in 10% stage I breast cancer disease, 20% stage II disease, 40% stage III disease, and 75% with stage IV disease (Duffy 2006). Elevated levels of this biomarker were detected among certain benign diseases, primary breast carcinoma (Coveney et al, 1995) and in patients with advanced adenocarcinomas (Anonymous, 1996;RESEARCH COMMUNICATION among females and increase the chance of breast cancer development (Crump et al, 2000;Rymer & Morris, 2000;Pike et al, 2004;Hulka & Moorman;2008), at the same time, serum CA15-3 level showed a significant increase within elderly menopause patients with breast cancer (Dehaghani et al, 2007). The aim of this study is to determine serum level of the tumor marker CA15-3 among Jordanian healthy, benign breast lesions and breast cancer females, as well as to highlight relationship between CA15-3 level with cancer onset age, menarche, menopause, body mass index (BMI), oral contraceptives (OCP), hormonal therapy (HT), tumor grade, stage and hormonal receptor status among breast cancer females.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of androgens allows the reduction of the dose of estrogen needed to control vasomotor symptoms or enhance mood improvement, whereas synthetic progestins (especially MPA) could be antagonistic to estrogen and mitigate its mood-enhancing effect [101,102]. Sequential HT may produce periodic increases in depressive and anxiety symptoms (which has been related to the progesterone metabolite allopregnanolone [103]), and this may improve with continuous combined HT therapy.…”
Section: Menopausal Htmentioning
confidence: 99%
“…Results from randomized placebo-controlled trials suggest ET improves quality of life, as estimated by standard quantitative tests (76). This improvement in general quality of life is likely due to improvement in vasomotor symptoms (44).…”
Section: Quality Of Life Sleep Mood and Depressionmentioning
confidence: 99%
“…The first systematic review of randomized controlled clinical trials found 40 trials showing that HT reduces the severity of vasomotor symptoms, often with improvement beginning within the first week of treatment (76). Summary estimates of hot-flash frequency and severity from another meta-analysis of the results of 21 trials of 3 months-3 years duration reported that standard doses of estrogen (equivalent to about 0.625 mg of conjugated estrogen) reduced weekly hot-flash frequency by 77%, compared with placebo (58).…”
Section: Clinical Trials Of Ht For Vasomotor Symptomsmentioning
confidence: 99%